Tailoring Two-Dimensional NiFeCo-Layered Double Hydroxide onto One-Dimensional N-Doped CNTs for High-Performance Bifunctional Air Electrodes in Flexible Zinc–Air Batteries - Yeon-Woo Kim; Ayeon Lee; Sung Hoon Ahn (Batteries)
The development of bifunctional air electrodes with high activity and durability is essential for advancing flexible zinc–air batteries. Herein, a hierarchical electrode structure is designed by growing N-doped carbon nanotubes (CNTs) on copper foam, where CNTs serve as highly active oxygen reduction reaction (ORR) sites. The controlled deposition of NiFeCo-layered double hydroxide (LDH) nanosheets, optimized to maintain ORR activity while enhancing oxygen evolution reaction (OER) performance, enables a finely tuned bifunctional catalyst. This architecture achieves outstanding electrochemical properties, requiring only 0.897 V vs. RHE and 1.446 V vs. RHE to reach 10 mA cm−2 in 1 M KOH, thereby minimizing overpotentials. When implemented as an air electrode in a quasi-solid-state zinc–air battery, the system demonstrates remarkable cycling stability, sustaining performance for over 300 h. Furthermore, a 16 cm2 pouch-type zinc–air battery delivers a high discharge capacity of 0.62 Ah, highlighting the scalability of this design. This work presents a robust and scalable strategy for developing high-performance bifunctional air electrodes, offering a promising route for next-generation flexible energy storage systems.